Sensorineural hearing loss in the opposite ear following head trauma - Tekin, Ahmet Mahmut; Soylu, Erkan; Altın, Gökhan; Yılmaz, Fahrettin; Haberal Can, İlknur (My University, 2016)
Sensorineural hearing loss following the head traumais one of the most common complications that mightoccur. Although radiological evidence that presents thelabyrinth damage as sensorineural hearing loss in somepatients complaining of these symptoms after thetrauma; cannot be determined. The underlyingmechanism is commonly assumed to be the concussionof the labyrinth that is frequently seen in headtraumas. In this paper, we would like to presentdouble?sided tinnitus and hearing loss that developedafter the head trauma due to the concussion of thelabyrinth in the opposite ear without temporal bonefractures.

Kafa travması sonrası işitme kaybı sık karşılaşılan komplikasyonlardan biridir.Travma sonrasında bu şikayetlerle gelen bazı hastalarda sensörinöral işitme kaybı için labirent hasarını gösteren radyolojik bir bulgu saptanamamakla beraber altta yatan mekanizmanın kafa travmalarında sıklıkla rastlanan labirentin konküzyonu olduğu varsayılmaktadır.Bu yazıda kafa travması sonrası temporal kemik fraktürü olmadan karşı kulakta labirentin konküzyon nedeniyle işitme kaybı ve çift taraflı tinnitus gelişmiş bir olguyu sunduk.
Kafa travması sonrası karşı kulakta sensörinöral işitme kaybı
Keywords: Labyrinth Concussion; Hearing Loss; Head Trauma; Labirent Konküzyonu; İşitme Kaybı; Kafa Travması